2011
DOI: 10.1007/s10551-011-0901-2
|View full text |Cite
|
Sign up to set email alerts
|

How Sustainability Ratings Might Deter ‘Greenwashing’: A Closer Look at Ethical Corporate Communication

Abstract: ABSTRACT. Of the many ethical corporate marketing practices, many firms use corporate social responsibility (CSR) communication to enhance their corporate image. Yet consumers, overwhelmed by these more or less well-founded CSR claims often have trouble identifying truly responsible firms. This confusion encourages "greenwashing" and may make CSR initiatives less effective. On the basis of attribution theory, this study investigates the role of independent sustainability ratings on consumers' responses to comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
505
3
31

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 641 publications
(554 citation statements)
references
References 82 publications
15
505
3
31
Order By: Relevance
“…Whereas internal CSR communication itself will thus rather be perceived as extrinsic, positive external CSR communication should drive attributions to intrinsic motives due to higher levels of credibility and trust (Parguel et al 2011;Becker-Olsen et al 2006). Prior research found that consumers are more likely to have negative attitudes, beliefs, and behaviors toward the organization when they assign extrinsic motives compared to intrinsic motives (Becker-Olsen et al 2006;Ellen et al 2006;Mohr et al 1998;Yoon et al 2006).…”
Section: The Mediating Role Of Motives: Attribution Theorymentioning
confidence: 99%
See 4 more Smart Citations
“…Whereas internal CSR communication itself will thus rather be perceived as extrinsic, positive external CSR communication should drive attributions to intrinsic motives due to higher levels of credibility and trust (Parguel et al 2011;Becker-Olsen et al 2006). Prior research found that consumers are more likely to have negative attitudes, beliefs, and behaviors toward the organization when they assign extrinsic motives compared to intrinsic motives (Becker-Olsen et al 2006;Ellen et al 2006;Mohr et al 1998;Yoon et al 2006).…”
Section: The Mediating Role Of Motives: Attribution Theorymentioning
confidence: 99%
“…This profusion of CSR labels, whether justified or not, makes it difficult to distinguish which label is certified by a third party (external CSR label), and hence provides a more objective assessment of a company's CSR efforts, and which label is uncertified (internal CSR claim; Nyilasy et al 2014;Parguel et al 2011). Therefore, it is also of interest to investigate how consumers respond to the combination of such an external multilevel environmental performance rating and internal CSR efforts controlled by the company.…”
Section: External Label Versus Internal Claimmentioning
confidence: 99%
See 3 more Smart Citations